The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.0001-6349.2004.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in vascular endothelial growth factor production associated with decidualization by human endometrial stromal cells in vitro

Abstract: VEGF production increased in association with decidualization in this in vitro study. Decidualization of ESCs may play a role in the induction of growth in the human fetus and/or placentation. The mechanism involved may include influencing the production of angiogenic growth factors such as VEGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The USCs isolated from the uterus on day 5 of pregnancy are proliferative in culture. Decidualization of USCs was induced by MPA and db-cAMP (Matsui et al 2004), and the strong expression of d/t PRP indicated the differentiating status of USCs. Indeed, there was marked difference in the pattern of Per2 oscillation between proliferative and decidualizing USCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The USCs isolated from the uterus on day 5 of pregnancy are proliferative in culture. Decidualization of USCs was induced by MPA and db-cAMP (Matsui et al 2004), and the strong expression of d/t PRP indicated the differentiating status of USCs. Indeed, there was marked difference in the pattern of Per2 oscillation between proliferative and decidualizing USCs.…”
Section: Discussionmentioning
confidence: 99%
“…The culture medium was replaced at 15 min after cell seeding to remove epithelial cells. In vitro decidualization of USCs was performed as previously described (Matsui et al 2004). Confluent USCs were further cultured for 6 days in DMEM/F12 supplemented with 2% FBS, 0 .…”
Section: Preparation and Culture Of Cellsmentioning
confidence: 99%
“…In addition, presence of gp130 (LIF receptor) has not been demonstrated in SCs, and GE has been shown as the resource of gp130 [24,25]. On the other hand, secretion of VEGF and VEGF mRNA arise from endometrial SCs [10,26]. In the present study, VEGF staining was observed in SCs and ECs, while LIF staining was observed in GE and LE in all groups.…”
Section: Discussionmentioning
confidence: 44%
“…Two of these factors, leukaemia inhibitory factor (LIF) and vascular endothelial growth factor (VEGF), are necessary in the implantation period. LIF, a member of the IL-6 family, is related to the development of the pinopode and implantation [9], and VEGF induces angiogenesis in the endometrium during the decidualisation period [10]. In addition, LIF, as a member of the inflammatory cytokine family, is a key mediator in various inflammatory processes such as acute-phase reaction, tissue damage and infection [11].…”
Section: Introductionmentioning
confidence: 99%
“…16 Briefly, MPA was dissolved in ethanol and db-cAMP was dissolved in filtered distilled water that had been added to the media before use. 16 Briefly, MPA was dissolved in ethanol and db-cAMP was dissolved in filtered distilled water that had been added to the media before use.…”
Section: Decidualization Of Human Escs In Vitromentioning
confidence: 99%